APAKAH PEMBELAJARAN ILMU WIRAUSAHA MAMPU MEMPERKUAT MOTIVASI MAHASISWA PROGRAM STUDI PSIKOLOGI BERWIRAUSAHA ? - Aji, Ambyah Atas; Setianingtyas, Anna Febrianty; Murjito, Winarno Heru; Prasetyo, Jarot; Santoso, Imam; Hersulastuti, Hersulastuti; Suranto, Much (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2023)
This research aimed to test whether the learning model obtained by Undergraduate Psychology students at Unwidha through entrepreneurship education can strengthen attitude variables, subjective norms and perceived behavioral control of interest in entrepreneurship. The research design used quantitative methods that explained the causal relationship between one variable and the other variables tested. The hypothesis test was formulated in a model using the Structural Equation Model multivariate test. The population in this research were all undergraduate psychology students at Unwidha who had a strong interest in entrepreneurship. The sampling technique was carried out by purposive sampling of 40 student respondents. The results of the analysis found that entrepreneurship education as a moderator can strengthen student entrepreneurship motivation and the overall model in the SEM fit test. The results of the research can be used as a basis for making a quality entrepreneurial learning model by adding aspects of real entrepreneurial practice for students of Psychology Unwidha in the future.